Keterampilan Menulis dan Berbicara Bahasa Jerman Siswa Berbasis Model Pembelajaran SAUD - Alvionicha, Finy; Jufri, Jufri; Dalle, Ambo (Universitas Negeri Makassar, 2021)
Abstract. This research is a pre-experimental design research which aims to determine the effectiveness of SAUD learning model in German language writing and speaking skills of class XI MIA MAN 1 Makassar. The data was collected through writing and speaking skills tests. Data were analyzed using paired sample t-test. The population of this research were students of class XI MIA MAN 1 Makassar, which consisted of 5 classes totaling 195 students. The sample was selected using purposive sampling technique. XI MIA 2, totaling 40 students was selected as the first experimental class and XI MIA 4 totaling 37 students was selected as the second experimental class. The results of data analysis of the first experimental class showed that tcount 8,78 > ttable 1,991 at a significance level 0,05, thus, the application of SAUD learning model was effective in German writing skills of class XI MIA MAN 1 Makassar. The results of data analysis of the second experimental class showed that tcount 12,11 > ttable 1,993 at a significance level 0,05, thus, the application of SAUD learning model was effective in the German speaking skills of class XI MIA MAN 1 Makassar.